2014
DOI: 10.1007/s10508-013-0238-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Explicit Online Media and Sexual Risk Among Men Who Have Sex with Men in the United States

Abstract: This study aimed to describe sexually explicit online media (SEOM) consumption among men who have sex with men (MSM) in the United States and examine associations between exposure to unprotected anal intercourse (UAI) in SEOM and engagement in both UAI and serodiscordant UAI. MSM in the U.S. who accessed a men-seeking-men website in the past year (N = 1,170) were recruited online for a cross-sectional, Internet-based survey of sexual risk and SEOM consumption. In the three months prior to interview, more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 36 publications
3
54
2
Order By: Relevance
“…Overall, unmarried males who consumed pornography were more likely to use condoms than unmarried nonconsumers, even after controlling for relevant demographic variables. This result contrasts with Nelson et al, 35 Eaton et al, 23 and Stein et al, 32 although this association was weak and inconsistent across time frames. In addition, this study did not differentiate participants based upon sexuality, whereas the above studies examined only MSM.…”
Section: Unsafe Sex Practices and Condom Usecontrasting
confidence: 65%
See 4 more Smart Citations
“…Overall, unmarried males who consumed pornography were more likely to use condoms than unmarried nonconsumers, even after controlling for relevant demographic variables. This result contrasts with Nelson et al, 35 Eaton et al, 23 and Stein et al, 32 although this association was weak and inconsistent across time frames. In addition, this study did not differentiate participants based upon sexuality, whereas the above studies examined only MSM.…”
Section: Unsafe Sex Practices and Condom Usecontrasting
confidence: 65%
“…In a community sample of HIV-negative men who have sex with men (MSM), Eaton et al 23 found that time spent viewing pornography was associated with the number of unprotected insertive anal acts, but not the number of unprotected receptive anal sex acts in the previous month. In a similar study, Stein 35 found that the odds of engaging in unprotected anal intercourse were higher as the amount of unprotected anal intercourse viewed in pornography increased. In addition, the odds of having knowingly engaged in serodiscordant unprotected anal intercourse were also higher for greater amounts of unprotected anal intercourse viewed in pornography.…”
Section: Unsafe Sex Practices and Condom Usementioning
confidence: 88%
See 3 more Smart Citations